Impact of the thickness of Nickel oxide film for nitrogen dioxide gas sensing Applications - Mezher, Sabah J.; Hassan, Ehssan S.; Hassan, Marwa Abdul Muhsien; Ameer, Firas S. A. (Kurdistan Journal of Applied Research, 2017)
Nickel oxide (NiO) thin films were formed by RF reactive magnetron sputtering onto glass substrates. The Argon and Oxygen partial pressure were (3.2×10-3 torr) and (2.12×10-2 torr) respectively at room temperature. The thickness of the films deposited was in the range of 50-150 nm. The thickness necessity structural, electrical and sensing properties of (NiO) films were methodically examined. X-ray diffraction method which shows polycrystalline landscape with preferred reflection peak at (200) plane. Scanning electron microscope analysis revealed that the growth of nanorods in all the films. The gas sensitivity of nitrogen dioxide gas was (67 %). It was observed that the gas sensitivity for (NiO) films was increased as film thickness increases.